Digital Media and Children - Seda Topçu; Tuğba Ayçiçek Dinçer (Galenos Publishing House, 2022)
Today, digital media occupies an important place in human life and children live in this technological environment. Exposure to excessive and inappropriate digital media content, especially in early childhood, when brain development is important, has negative effects both in childhood and adulthood. Excessive and poor quality digital media use has been found to be associated with early effects such as sleep problems, negative self-regulation skills, cyberbullying, psychological disorders, and adult diseases such as obesity and cardiovascular disease. In the light of these data, the American Academy of Pediatrics does not recommend screen use for children before 18 months, except for video chat. It is important for parents to choose quality content in the use of digital media, to be a role model for their children, to guide them and to keep in touch with their children while using the screen.